Arc connectivity of transformation digraph Dxyz*. (3rd March 2016) - Li, Jing-Jing; Liu, Juan
Abstract: A simple digraph D (without loops and multiple arcs)is said to be super-arc-connected if every minimum arc-cut is the out-neighbor set or in-neighbor set of a vertex. In this paper, we investigate the arc connectivity of these ten kinds of new total transformation digraphs associate with symbol '0'.